2019
DOI: 10.1177/8756479319856283
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic Assessment of Heel Pad Thickness in Patients With Poorly Controlled Diabetes

Abstract: The aim was to compare the heel pad thickness (HPT) in diabetic patients with high biochemical parameters (fasting blood sugar [FBS], hemoglobin A1c [HbA1c], and lipid profile) with nondiabetic counterparts. A total of 438 subjects made up of 216 diabetics with high biochemical parameters (poorly controlled) and 222 apparently healthy subjects were recruited. The HPT, FBS level, HbA1c values and lipid profile, and duration of diabetes mellitus were assessed. Results showed that the mean HPT was 13.33 ± 1.29 mm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…The mean HPT of males in the study done by Udoh et al . [ 21 ] among healthy Nigerians was 14.3 ± 1.24 mm while that of the females was 12.14 ± 1.26 mm which were similar to what was obtained in the index study where the average HPT in the nondiabetic males and females participants measured 14.6 ± 1.71 mm and 13.7 ± 1.06 mm respectively.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The mean HPT of males in the study done by Udoh et al . [ 21 ] among healthy Nigerians was 14.3 ± 1.24 mm while that of the females was 12.14 ± 1.26 mm which were similar to what was obtained in the index study where the average HPT in the nondiabetic males and females participants measured 14.6 ± 1.71 mm and 13.7 ± 1.06 mm respectively.…”
Section: Discussionsupporting
confidence: 85%
“…This is similar to what was found in the index study ( P = 0.9633) but incongruent to the findings by Udoh et al . [ 21 ] where analysis of variance showed that there was a significant difference between the value of HPT obtained from the male subjects and those obtained from the females. This could be due to the difference in the subject sample size and probably because the study was carried out among healthy Nigerians only.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, from the close‐up photographs that exist of bound feet (Fig. B , D , asterisk), it appears that the adipose pad in the heel could be unusually thick compared to its normal thickness in females, as reported to be about 12 mm . Compensatory thickening of the heel fat pad has also been observed to occur within 2 years following a foot trauma that reduces mobility of the ankle .…”
Section: Discussionmentioning
confidence: 89%
“…1B, D, asterisk), it appears that the adipose pad in the heel could be unusually thick compared to its normal thickness in females, as reported to be about 12 mm. (31) Compensatory thickening of the heel fat pad has also been observed to occur within 2 years following a foot trauma that reduces mobility of the ankle. (32) It follows that soft tissue adaptation compensates for the deficiency of the shock-dampening function of the bones of the foot.…”
Section: Discussionmentioning
confidence: 99%
“…
The incidence of diabetes mellitus (DM) is growing rapidly worldwide, [1][2][3] with the global estimate at 171 million as of 2020. 4 In Nigeria, more than 30% of the elite population including decision makers are diabetic, 5,6 and the risk of developing associated complications and mortality is higher with poorer hyperglycemia control. 7 Several studies have been tailored toward early diagnosis and mitigation of complications of DM.
…”
mentioning
confidence: 99%